2010
DOI: 10.1080/09500690903518060
|View full text |Cite
|
Sign up to set email alerts
|

Philosophical Approaches of Religious Jewish Science Teachers Toward the Teaching of ‘Controversial’ Topics in Science

Abstract: This research examines the problems that religious Jewish science teachers in Israeli high schools have in coping with science subjects (such as geological time) which conflict with their religious beliefs. We do this by characterizing the philosophical approaches within Judaism that such teachers have adopted for dealing with such controversy. Thus, we surveyed 56 religious teachers using a Likert-type questionnaire developed for this research, as well as interviewed 11 teachers to more deeply probe their app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…However, teachers with moderate convictions often accept some evolutionary topics while rejecting others. Teachers who feel some conflict between their religious beliefs and evolution tend to accept the mechanisms of evolution, but believe there is an ultimate creator or greater purpose to the process (Dodick et al 2010;Goldston and Kyzer 2009;Meadows et al 2000;Winslow et al 2011). Tomczyk and Bugajak (2009) found that 80% of Polish teachers who believed in an ultimate aim of evolution saw no conflict between religion and evolution because they could reconcile evolution within their teleological viewpoints.…”
Section: Factors Associated With Acceptancementioning
confidence: 99%
“…However, teachers with moderate convictions often accept some evolutionary topics while rejecting others. Teachers who feel some conflict between their religious beliefs and evolution tend to accept the mechanisms of evolution, but believe there is an ultimate creator or greater purpose to the process (Dodick et al 2010;Goldston and Kyzer 2009;Meadows et al 2000;Winslow et al 2011). Tomczyk and Bugajak (2009) found that 80% of Polish teachers who believed in an ultimate aim of evolution saw no conflict between religion and evolution because they could reconcile evolution within their teleological viewpoints.…”
Section: Factors Associated With Acceptancementioning
confidence: 99%
“…Susan also specifically addressed common misconceptions about evolution (Hermann, 2013;Sanders & Ngxola, 2009). Susan took a complementary approach, presenting evolution as not necessarily exclusive of religion (Chuang, 2003;Dodick et al, 2010;Hanley et al, 2014). Finally, Susan explicitly told students that they needed to understand but not necessarily accept evolution (Bramschreiber, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Biology teachers sometimes reject evolution (Kim & Nehm, 2011;Nehm et al, 2009;Nunez et al, 2012), are doubtful of the scientific community's acceptance of evolution (Kim & Nehm, 2011), and perceive conflict between evolution and their own religious perspectives (Dodick et al, 2010;Kim & Nehm, 2011;Nehm et al, 2009). Teacher acceptance of evolution has been positively associated with sophistication of NOS views (Kim & Nehm, 2011), negatively associated with religiosity (Nehm et al, 2009), and positively associated with use of a standardized curriculum (Nunez et al, 2012).…”
Section: Teacher Difficulties For Teaching Evolutionmentioning
confidence: 94%
See 1 more Smart Citation
“…Religious teachers are not necessarily creationist, as Dodick et al (2010) found that a majority of mamlakhti‐dati teachers feel that evolution does not contradict their religious beliefs. Nevertheless, evidence suggests there is still a distinct divide between the treatment of evolution in mamlakhti and mamlakhti‐dati schools.…”
mentioning
confidence: 99%